2022
DOI: 10.2196/37635
|View full text |Cite
|
Sign up to set email alerts
|

Emotions and Incivility in Vaccine Mandate Discourse: Natural Language Processing Insights

Abstract: Background Despite vaccine availability, vaccine hesitancy has inhibited public health officials’ efforts to mitigate the COVID-19 pandemic in the United States. Although some US elected officials have responded by issuing vaccine mandates, others have amplified vaccine hesitancy by broadcasting messages that minimize vaccine efficacy. The politically polarized nature of COVID-19 information on social media has given rise to incivility, wherein health attitudes often hinge more on political ideolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…Ultimately, we argue that the antecedents of incivility can inform public health interventions. Existing studies have found a link between incivility and negative emotions such as sadness and anxiety [ 20 ]. Therefore, public health messaging that evokes such emotions could result in uncivil discourse from the public.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, we argue that the antecedents of incivility can inform public health interventions. Existing studies have found a link between incivility and negative emotions such as sadness and anxiety [ 20 ]. Therefore, public health messaging that evokes such emotions could result in uncivil discourse from the public.…”
Section: Discussionmentioning
confidence: 99%
“…Perspective application programming interface (API), a tool that uses machine learning to detect comment incivility, was used to measure 5 dimensions of incivility, namely, toxicity, insults, profanity, threat, and identity attack (see Textbox 3 for definitions and examples). Perspective API is a validated tool trained by human coders on large data sets with millions of comments and has been used in studies across various contexts, such as health and politics [ 17 , 20 , 63 , 64 ]. Perspective API assigns each comment a score from 0 to 1 per dimension of incivility based on how closely the comment reflected the specific dimension and how likely it was to impact a conversation.…”
Section: Methodsmentioning
confidence: 99%
“…Each model, for every given input text, yields a score from 0 to 1 representing the intensity of a type of misbehavior. We retrieve scores from the 6 production-ready Perspective API models [51]:…”
Section: Dataset Augmentation With Perspective Apimentioning
confidence: 99%
“…In terms of patient characteristics, some research indicates that the emotional state of a patient greatly influences their likelihood to behave with incivility. Two emotions are most strongly associated with an increased incidence of incivility: anger and sadness [ 14 ]. Specifically, anger has been linked to an increased likelihood of “profanity, insults,... identity attacks, and threats” while sadness increases the likelihood of threats [ 14 ].…”
Section: Reviewmentioning
confidence: 99%